Measuring The Effects of Fiscal Shocks on Civil Servant Performance: An Empirical Study of The Riau Provincial Government with Perceived Organizational Support (POS) As The Moderator - Safrizal Safrizal; Meilinda Anggreni; Novira Fazri Nanda; Twenty Mariza Syafitri (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2026)
This study aims to measure the effect of fiscal shocks on the performance of State Civil Apparatus (ASN) within the Riau Provincial Government, and examine the role of Perceived Organizational Support (POS) as a moderating variable. Fiscal shocks, manifested through late salary payments, limited work facilities, operational cuts, and budget policy uncertainty, are viewed as external pressures that have the potential to reduce ASN performance, both in terms of productivity, work efficiency, and public service. In this context, Perceived Organizational Support (POS), which indicates that the organization cares about their welfare and contributions, is positioned as a variable that can strengthen or weaken the relationship between fiscal shocks and employee performance. ASN who perceive high organizational support tend to have better psychological resilience in facing fiscal pressure, thus being able to maintain performance. This study uses a quantitative approach with a questionnaire, involving ASN from the Public Works and Public Housing (PUPR) OPD in the Riau Provincial Government as respondents. Data analysis was conducted using Moderating Regression Analysis to test the direct influence and moderating effects. This research is expected to provide practical contributions for local governments in designing adaptive ASN management strategies amidst fiscal pressures, as well as strengthening internal policies related to organizational support so that employee performance is maintained in situations full of uncertainty